Development of a rehabilitation robot for hand and wrist rehabilitation training - Chunbao Wang; Zhijiang Lu; Yulong Wang; Mengjie Li; Lihong Duan; Yajing Shen; Jianjun Wei; Qing Shi; Massimiliano Zecca; Weiguang Li; Zhengzhi Wu (2015)
Up to now, the number of hemiplegia rehabilitation devices is increasing quickly along with hemiplegic patients'. But most of hand rehabilitation training just limit to the fingers flexible training of patients' affected hand. They not only ignore the importance of functional training of hand, but also wrist cooperative training during rehabilitation process. In our new research, we proposed a novel hand and wrist rehabilitation robot to achieve grasp functional training of hand except thumb and intorsion/extorsion and dorsiflexion/plantar flexion of wrist, which provides a creative hand rehabilitation way for hemiplegic patients. In this paper, we will introduce the detail design of the robot. It mainly includes two rehabilitation units - wrist rehabilitation unit and hand rehabilitation unit, which can realize separate motion or cooperate motion of hand and wrist based on patients' willingness. What's more, the torque sensor unit is purposely designed to detect feedback torque of related motion instead of available ones in the market, which makes the whole mechanical structure more compact. In a word, this novel hand and wrist rehabilitation robot will have a promising prospect.